Study on corporate strategies adopted by Indian passenger car manufacturers - Gupta, Saurabh (2007)
ABSTRACT Corporate strategy is a very challenging subject in the todays world and its significance is being recognized gradually in theoretically as well in practical application. There have been various studies showing the positive effect of corporate strategies on the performance of large automobile players. But there has not been enough research about the use of strategies in the Indian car industry. This research studies the corporate strategies of Indian passenger car manufacturers. The purpose of this analysis is to present the growth and development strategies of Indian car manufacturers like Maruti and Tata Motors. This study also determines reasons for the downfall of companies like Hindustan Motors and Premier Automobile Limited. This study uses the case study methodology of research. All relevant information regarding the history, growth, financial position and overall corporate strategies used by these four companies have been collected from secondary sources of data. These secondary include published annual reports, trade magazines, websites, newspaper and other relevant information collected from the market. The main reason for conducting this research is to investigate and analyze the reasons that led to growth & decline of these companies. And to determine the strengths and weaknesses of these companies.